Studies of Cellulose and Starch Utilization and the Regulatory Mechanisms of Related Enzymes in Fungi - Wang, Bao-Teng; Hu, Shuang; Yu, Xing-Ye; Jin, Long; Zhu, Yun-Jia; Jin, Feng-Jie (Polymers, 2020)
Polysaccharides are biopolymers made up of a large number of monosaccharides joined together by glycosidic bonds. Polysaccharides are widely distributed in nature: Some, such as peptidoglycan and cellulose, are the components that make up the cell walls of bacteria and plants, and some, such as starch and glycogen, are used as carbohydrate storage in plants and animals. Fungi exist in a variety of natural environments and can exploit a wide range of carbon sources. They play a crucial role in the global carbon cycle because of their ability to break down plant biomass, which is composed primarily of cell wall polysaccharides, including cellulose, hemicellulose, and pectin. Fungi produce a variety of enzymes that in combination degrade cell wall polysaccharides into different monosaccharides. Starch, the main component of grain, is also a polysaccharide that can be broken down into monosaccharides by fungi. These monosaccharides can be used for energy or as precursors for the biosynthesis of biomolecules through a series of enzymatic reactions. Industrial fermentation by microbes has been widely used to produce traditional foods, beverages, and biofuels from starch and to a lesser extent plant biomass. This review focuses on the degradation and utilization of plant homopolysaccharides, cellulose and starch; summarizes the activities of the enzymes involved and the regulation of the induction of the enzymes in well-studied filamentous fungi.